FIGURE 11 in A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska - Bekker, Eugeniya I.; Kotov, Alexey A.; Taylor, Derek J. (Zenodo, 2012)
FIGURE 11. Eurycercus beringi sp.nov., head and thoracic appendages of parthenogenetic female from Council #05: a roadside pond <1.5 m deep, 10 X 25 m, Seward Peninsula, Alaska, U.S.A. A, antenna I. B, antenna II. C, limb I. D, inner distal lobe of limb I. E, limb II. F, distal armature of its gnathobase. G, limb III. H, limb IV. I, distal armature of its gnathobase. J, limb V. K, distal armature of its gnathobase. K, limb VI. Scale bar denotes 0.1 mm. : Published as part of Bekker, Eugeniya I., Kotov, Alexey A. & Taylor, Derek J., 2012, A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska, pp. 1-40 in Zootaxa 3206 (1) on page 31, DOI: 10.11646/zootaxa.3206.1.1, http://zenodo.org/record/5248211